La educación musical en el desarrollo rítmico-auditivo de los niños y niñas del 4to., 5to. y 6to. años de educación básica de la escuela fisco misional Balbina Moreno del cantón Gonzanamá. Periodo 2014-2015 - Bravo Álvarez, Patricia Marina (2016)
This research has been an essential part in the musical development of students, which had as its overall objective to develop and identify rítmico- auditory skills of children of school Fiscomisional Balbina Moreno through the formation of a group instruments belonging to the institution, to the effect, the population was delimited to investigate methods and techniques for this as the survey and interview were used, the survey was applied to 13 teachers, an interview with the director of the campus and heading instrument 75 hearing children of the institution, totaling 89 people, the results obtained it can be stated that 100% believe that there is a musical group, results that allowed us to make a proposal at the institution rítmico- skills, which it was the creation of an instrumental group children of the 4th, 5th, and 6th years of primary school education Fiscomisional Balbina Moreno Canton Gonzanamá. The conclusion is that music education is important in the curriculum of study in each school, as it allows to discover, develop musical rhythm-listening skills of children and especially rescue artistic and human values, for this reason, it is recommended to Office officials, maintain and strengthen the instrumental group as a means of enjoyment and learning so that it can enrich the musical knowledge of the students in their education.